Natriuresis-guided diuretic therapy in acute heart failure: a pragmatic randomized trial - ter Maaten, Jozine M.; Beldhuis, Iris E.; van der Meer, Peter; Krikken, Jan A.; Postmus, Douwe; Coster, Jenifer E.; Nieuwland, Wybe; van Veldhuisen, Dirk J.; Voors, Adriaan A.; Damman, Kevin (Nature medicine, 2023)
Measurement of natriuresis has been suggested as a reliable, easily obtainable biomarker for assessment of the response to diuretic treatment in patients with acute heart failure (AHF). Here, to assess whether natriuresis-guided diuretic therapy in patients with AHF improves natriuresis and clinical outcomes, we conducted the pragmatic, open-label Pragmatic Urinary Sodium-based algoritHm in Acute Heart Failure trial, in which 310 patients (45% female) with AHF requiring treatment with intravenous loop diuretics were randomly assigned to natriuresis-guided therapy or standard of care (SOC). In the natriuresis-guided arm, natriuresis was determined at set timepoints, prompting treatment intensification if spot urinary sodium levels were <70 mmol l −1 . The dual primary endpoints were 24 h urinary sodium excretion and a combined endpoint of time to all-cause mortality or adjudicated heart failure rehospitalization at 180 days. The first primary endpoint was met, as natriuresis in the natriuresis-guided and SOC arms was 409 ± 178 mmol arm versus 345 ± 202 mmol, respectively ( P = 0.0061). However, there were no significant differences between the two arms for the combined endpoint of time to all-cause mortality or first heart failure rehospitalization, which occurred in 46 (31%) and 50 (31%) of patients in the natriuresis-guided and SOC arms, respectively (hazard ratio 0.92 [95% confidence interval 0.62–1.38], P = 0.6980). These findings suggest that natriuresis-guided therapy could be a first step towards personalized treatment of AHF. ClinicalTrials.gov registration: NCT04606927 . In patients with acute heart failure, personalized dosing of a diuretic led to treatment intensification in the majority of patients and improved natriuresis, but had no effects on time to all-cause mortality or heart failure rehospitalization.